Perancangan Sistem Informasi Absensi Guru Berbasis Web di MTs Al-Azhar Legari - Ester Ayuk Pusvita; Muhammad Rofiq; Arief Rahman Hakim (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Teacher attendance is an important part in supporting the smooth running of teaching and learning activities in the school environment. At MTs Al-Azhar Legari, the attendance system that is still manual often causes obstacles such as delays in data recapitulation, inaccurate information, and difficulties in monitoring attendance efficiently. Therefore, this study aims to design and develop a web-based teacher attendance system that can improve the effectiveness and accuracy of attendance recording. The system is built using the PHP programming language and MySQL database, which facilitates the centralization of attendance data in real time. The test results show that the developed system is able to run well, provide convenience in managing attendance data, and support transparency and accountability in the school environment. With the presence of this system, it is hoped that the administrative process of teacher attendance at MTs Al-Azhar Legari can be more efficient, integrated, and able to minimize recording errors. In addition, this system can also be used as a basis for development towards a broader and more modern digitization of school administration.